2021
DOI: 10.3390/cells10092435
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Immunosenescence in Aging, Obesity, and Cardiovascular Disease

Abstract: Although advances in preventive medicine have greatly improved prognosis, cardiovascular disease (CVD) remains the leading cause of death worldwide. This clearly indicates that there remain residual cardiovascular risks that have not been targeted by conventional therapies. The results of multiple animal studies and clinical trials clearly indicate that inflammation is the most important residual risk and a potential target for CVD prevention. The immune cell network is intricately regulated to maintain homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 158 publications
(234 reference statements)
0
39
0
Order By: Relevance
“…Considering that, we then evaluated the distribution of CD4+ and CD8+ T cell subsets in the patient under study and sex and age-matched healthy control individuals. CD45RA and CCR7 cell surface markers were used to identify four phenotypically and functionally distinct subsets of CD4+ and CD8+ T-cells: naïve (Naïve: CD45RA+ CCR7+), central memory (CM: CD45RA- CCR7+), effector memory (EM: CD45RA- CCR7-) and terminally differentiated effector memory (TEMRA: CD45RA+ CCR7-) ( Figures 3A–C ) as previously reported ( 34 36 ). Figure 3B shows that, within the CD4+ T-cell compartment, the frequency of naïve and CM T cells were significantly lower in the patient than in controls (p<0.01).…”
Section: Case Descriptionmentioning
confidence: 72%
“…Considering that, we then evaluated the distribution of CD4+ and CD8+ T cell subsets in the patient under study and sex and age-matched healthy control individuals. CD45RA and CCR7 cell surface markers were used to identify four phenotypically and functionally distinct subsets of CD4+ and CD8+ T-cells: naïve (Naïve: CD45RA+ CCR7+), central memory (CM: CD45RA- CCR7+), effector memory (EM: CD45RA- CCR7-) and terminally differentiated effector memory (TEMRA: CD45RA+ CCR7-) ( Figures 3A–C ) as previously reported ( 34 36 ). Figure 3B shows that, within the CD4+ T-cell compartment, the frequency of naïve and CM T cells were significantly lower in the patient than in controls (p<0.01).…”
Section: Case Descriptionmentioning
confidence: 72%
“…Over time, scientific evidences have elucidated that obesity is a complex disorder and a major risk factor for many diseases and health problems such as cardiovascular diseases, T2D, cancer, among others (31). Additionally, based on similar characteristics for cellular senescence as those observed in aging, obesity has been linked to the development of early immunosenescence and decreases in life span (12)(13)(14)(15)31). In animal models used in experimentation, Hunsche et al (5) observed that macrophage and lymphocyte chemotaxis, macrophage phagocytosis, NK cell activity, lymphocyte proliferative response, secretion of IL-1b, TNF-a, IL-6, IL-2 and IL-10 in leukocyte cultures, as well as the antioxidant and oxidative capacity of obese adult rats were significantly impaired when compared to non-obese adult rats and similar to elderly rats, thus concluding that obesity can generate premature immunosenescence that is aggravated as the obese adult rat ages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increase evidence suggests that the process of aging is the result of the accumulation of cellular damage caused by oxidative and inflammation stress throughout the lifetime of an organism, where the immune system seems to be involved in this stress and in the rate of aging (5,11). Thus, given the context of neuro-immune-endocrine communication and its changes in oxidative and inflammatory situations, as well as the impairment of the immune system, characteristics similar to those observed in aging, it has been speculated that obesity generates premature immunosenescence (biological aging of the immune system), and this may be one of the reasons for the increased rate of morbidity and risk of death related to this disease (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI is often used to measure obesity, which is defined by the World Health Organization as having a BMI ≥ 30 [ 3 ]. Obesity has been identified as an independent risk factor for cardiovascular diseases in the context of increasing morbidity and mortality [ 4 , 5 ]. The essence of obesity is the abnormal accumulation of lipids and the increase in inflammatory factors in the body, which will inevitably augment the workload and impair the function of the heart and lungs.…”
Section: Introductionmentioning
confidence: 99%